How Important is the Application of Balanced Scorecard, Benchmarking and Data Envelope Analysis Techniques in Measuring Performance Efficiency in Private Banks/ Applied Study - Zainab Rasheed Ahmed ,RaeedMajeed AbdMohammed (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In view of the continuous developments and changes in the competitive business environment, the importance of Strategic Management Accounting is highlighted in the great role it plays in various economic units in terms of measuring the efficiency of performance on the one hand and evaluating it on the other, and comparing the efficiency of its performance with another leading economic unit in the same field. This research is aimed mainly at identifying the importance of some strategic management accounting methods (BSC balanced scorecard, BM Bench Marking) as well as the quantitative method of Operations Research Methods, which is the method of data envelope analysis (DEA) and their role in measuring the efficiency of performance in Iraqi private banks (al Mansour Investment Bank, Commercial Gulf Bank, Middle East Bank, National Bank of Iraq) and for the period of time (2015-2019) during the fixed volume returns model (CCR) method of data envelopment analysis, as well as the comparison between the banks of the research sample, and used the researcher descriptive analytical in financial ratio analysis that was used in the Balanced Scorecard, as well as statistical methods that have been used for data processing (arithmetic mean, median, token, bow, architecture, variance, range).The researcher reached a series of conclusions, most notably that the results of the statistical analysis showed that there is a relative difference in relative efficiency according to the perspectives of the balanced scorecard and for different years. There is a near-equal in the computational circles of the financial performance of the research sample banks. The results of the statistical analysis showed that there is a close relationship between the Balanced Scorecard binoculars and the data envelope analysismethod, the latter complementary to the Balanced Scorecard work in measuring performance efficiency.